3D printing for cardiovascular tissue engineering: a review. (12th May 2018) - Roy, Abhishek; Saxena, Varun; Pandey, Lalit M.
Abstract: Although the current medical treatments have been successful in reducing the coronary heart disease related mortality rate, however there still exist various challenges in cardiac tissue engineering due to the hierarchical property of native myocardium and branched structure of blood vessels. The regeneration of progenitor cells, replacement infarcted cardiac tissues and the tissue-engineered constructs are the demand of the current era. In this contrast, 3D printing of scaffold for cardiac tissue engineering plays a crucial role. 3D printing techniques are used to generate patient-specific foundation that mimics the milieu of biological tissue. Various studies are under investigation to regenerate the cardiac tissues. Lack of regeneration capacity is a major hunt in cardiac tissue engineering. This review will provide an overview of 3D bioprinting techniques for cardiovascular tissue engineering. First, it summarises the background about bioprinting (working principles) followed by various bioink materials for cardiac tissue engineering. Recent approaches for the 3D printing of cardiac scaffolds for the regeneration of cardiac tissues are discussed.